Some features of the behaviour of the marbled newt Triturus marmoratus (Latreille, 1800) in captivity - Robalo, Joana Isabel (2012)
The behaviour in groups of both sexes of marbled newts (Triturus marmoratus) from Sintra, Portugal, kept for a few weeks in a large aquarium, is described. Behaviour patterns described for this species and for other species in this genus were recognised. The following behaviours are described for the first time: Walk-over, Land-over, Stand-on, Show, Erect-body, Yawn, Circle, and Dig. Females seem to have a more active role in courtship than is usually considered. The behaviour frequencies for each sex were analysed using simulation statistics. Some elements usually classified as male sexual behaviours occur in both sexes and are likely to play other social roles.